Economic Analysis of Law: Strengthening the Legal Framework for Development - Widijowati, Dijan (LifeSciFi, 2023)
In the context of development, an adequate legal framework plays a crucial role in creating a conducive and attractive business climate for investors, both domestic and international. The existence of a clear and consistent law gives confidence to economic actors that their rights will be recognized, protected and defended. By using the Economic Analysis of Law approach, efficiency is an ideal guide in designing legal policies. However, there are challenges and complexities associated with strengthening the legal framework for development. Some of the problems that often arise include the weakness of the justice system, corruption, legal uncertainty, and unequal access to justice. This research will try to see how legal economic analysis can be used as a tool to strengthen a country's legal framework in a development context. This study applies a normative juridical approachin order to analyze and interpret applicable law and understand the relevant legal norms. The results show that law plays a very important role in economic development. The law provides a clear and reliable framework for economic actors, protects propertyrights, and guarantees the protection of economic contracts and transactions. The Economic Analysis of Law (EAL) approach and the role of law in economic development are interrelated and influence each other. Through the Analysis of Law approach, an analysis based on legal values, benefits and efficiency can make an important contribution in strengthening the legal framework for more effective and efficient development.